Goal Oriented Behavior With a Habit-Based Adaptive Sensorimotor Map Network - Woolford, Felix M. G.; Egbert, Matthew D. (Frontiers in Neurorobotics, 2022)
We present a description of an ASM-network, a new habit-based robot controller model consisting of a network of adaptive sensorimotor maps. This model draws upon recent theoretical developments in enactive cognition concerning habit and agency at the sensorimotor level. It aims to provide a platform for experimental investigation into the relationship between networked organisations of habits and cognitive behaviour. It does this by combining (1) a basic mechanism of generating continuous motor activity as a function of historical sensorimotor trajectories with (2) an evaluative mechanism which reinforces or weakens those historical trajectories as a function of their support of a higher-order structure of higher-order sensorimotor coordinations. After describing the model, we then present the results of applying this model in the context of a well-known minimal cognition task involving object discrimination. In our version of this experiment, an individual robot is able to learn the task through a combination of exploration through random movements and repetition of historic trajectories which support the structure of a pre-given network of sensorimotor coordinations. The experimental results illustrate how, utilising enactive principles, a robot can display recognisable learning behaviour without explicit representational mechanisms or extraneous fitness variables. Instead, our model’s behaviour adapts according to the internal requirements of the action-generating mechanism itself.